The Corelations of Loneliness with Social Media Addiction to Academic Procrastination in Adolescents - Isa Alvia; Sri Saparahayuningsih; Rita Sinthia (Universitas PGRI Yogyakarta, 2024)
This study aims to determine the corrlation between loneliness and social media addiction to academic procrastination. The sampling technique used in this study is purposive sampling. The population of this study was all students of SMKN 3 Seluma with a total sample of 247 students taken based on predetermined criteria. Data were obtained through questionnaire distribution and analyzed using descriptive quantitative methods and analyzed using Product Moment test. The results showed that the loneliness variable had a positive influence on academic procrastination, which was 0.768, while the social media addiction variable had a positive effect on academic procrastination with a correlation coefficient value of 0.849 and loneliness had a significant positive effect on social media addiction with a correlation coefficient value of 0.767. So it can be concluded that loneliness and social media addiction have a significant positive corelation with academic procrastination. Keywords: loneliness, social media addiction, academic procrastination